Russian influence works – also in Denmark - Serritzlev, Jeanette (Politica, 2023)
The article looks at Russian influence in Denmark and seeks to put Russia’s use of influence and information activities outside Russia as a means to achieve foreign policy strategic goals into a larger context. This happens e.g. by creating discord in the West. Russia achieves this, among other things, by means of modern propaganda principles of distributing the messages constantly, massively and repeatedly. The article’s argument is that Russian influence can reach Danish media users in several ways and across platforms. This has become especially clear after the Russian invasion of Ukraine, where former COVID skeptics have largely taken over pro-Kremlin narratives. It is, as the chronicle will unfold, not accidental.